EFEKTIFITAS PENGGUNAAN WEB BASED LEARNING PADA MATAKULIAH PRAKTIKUM STRUKTUR DATA DENGAN BAHASA C++ - Nurul Adha Oktarini Saputri; Merrieayu Puspita Hannah; Heri Suroyo (Jurnal Informatika, 2017)
This study aims to measure and examine how the effectiveness of the use of web-based learning in the course practicum data structure. Web-based learning (web-based learning) that will be used in this study is a web tutorial address www.tutorialspoint.com. While the programming language to be studied on the web tutorial is a C ++ programming language tutorial. The methodology used in this research is Research Development with tutorial web-based instructional products for practical data structure course. The result of this research is first that is learning with web-based learning in practice subject which suitable to apply for new student group taking the course and the student who repeat the course. Second, the perception of the effectiveness of learning with web-based learning is higher in the group of students whose long internet access is high and in the group of students who study while working. Third, found the influence of the effectiveness of the use of web-based learning in learning to learn outcomes. Keywords: Web-based learning, Effectiveness of web base-learning, Data Structure and Language C ++